Long-Acting Composite Systems Based on Powdered Medicinal Plants and Nanosilica - Turov, V.V.; Krupska, T.V.; Golovan, A.P.; Andriyko, L.S.; Kartel, M.T. (Science and Innovation, 2024)
The state of water in the powdered plant materials (calendula, hibiscus) and their composite systems with A-300 nanosilicas having different bulk density has been studied by low-temperature 1H NMR spectroscopy method. The change in bulk density has been found to significantly affect the radius of inner cavities in fibrillar space of plant components. The composite systems based on wetting-drying compaction of nanosilica and plant powder have been showed to form a mix with high interaction energy of heterogeneous particles. This results in the effective retention of plant bioactive complex by composite, which enables the development of long-acting herbal drugs.